Unveiling The Influence of Free and Encapsulated Essential Oils Carried in Carnauba Wax Nanoemulsion: Physicochemical and Microbiological Properties - Procopio, Fernanda Ramalho; Brexó, Ramon Peres; Martins, Giulia Suguimoto; Fukuyama, Conny W. T.; da Mata Martins, Maria Eduarda [UNESP]; Bogusz Junior, Stanislau; Ferreira, Marcos David (Springer Nature, 2025)
Food loss due to microbial spoilage is a major global concern, particularly affecting the shelf life of fresh produce. Carnauba wax-based nanoemulsions have shown promise as edible coatings, especially when enriched with bioactive compounds such as essential oils (EOs). However, the high volatility and sensitivity of EOs to environmental conditions may compromise their antifungal activity. This study explores the incorporation of both free and β-cyclodextrin-encapsulated EOs including oregano, clove, palmarosa, peppermint, lemongrass, and spearmint into carnauba wax nanoemulsions to investigate stability and antimicrobial efficacy. A distinctive feature of this work is the application of solvatochromism to characterize EO polarity and support the interpretation of their interactions with the nanoemulsion matrix and antimicrobial outcomes. The formulations were evaluated for particle size, zeta potential, viscosity, morphology, and EO polarity. Their antimicrobial potential was tested in vitro against Escherichia coli, Staphylococcus aureus, and five phytopathogenic fungi: Colletotrichum sp., Fusarium solani, Rhizopus stolonifer, Lasiodiplodia theobromae, and Penicillium expansum. Results revealed that all formulations exhibited alkaline pH and zeta potential above -40 mV. Formulations with free EOs showed particle sizes ranging from 40–60 nm and low polydispersity indices (0.2–0.3). Encapsulation increased particle size (300–500 nm), PDI, and viscosity in nanoemulsion system. Antifungal activity was more pronounced in nanoemulsions containing free oregano and clove EOs. According to solvatochromism data, these EOs exhibited higher polarity, supporting hypotheses about polarity-influence on antimicrobial mechanisms. Overall, the findings offer valuable insights for the future design of more effective and sustainable edible coatings for postharvest fruit and vegetable preservation.